Correlation of Changes in Waste Generation in the Year Before and During the Pandemic in Surakarta City - SARI, Mega Mutiara; SEPTIARIVA, Iva Yenis; SURYAWAN, I Wayan Koko (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022DO - 10.14505/jemt.v13.3(59).08, 2022)
The city of Surakarta is one of the major cities in Indonesia that has been affected by COVID-19 with a high number of cases compared to cities in Central Java Province. The existence of COVID-19 not only has an impact on the health of the local community but also causes environmental problems. Therefore, to overcome these problems, a study was carried out on the effect of COVID-19 on changes in waste generation in Surakarta City. In this study, data were collected from local government inventory data, hypotheses, and data analysis using ANOVA. Based on the results of the study, it is known that the generation of domestic waste continues to increase during the pandemic, while the generation of waste in several public facilities such as transportation, parks, public places, and the Trade Office has decreased. The ANOVA analysis also shows that changes in the waste generation before and during the pandemic in Surakarta City were caused by changes in waste generation produced by domestic households and the government (Trade Department) while for other public facilities it did not affect these changes.